Development of a Model Mutagenesis System for Snapdragon - Zhaoyuan Lian; Heqiang Huo; Sandra B. Wilson; Jianjun Chen (EDIS, 2020)
Snapdragon (Antirrhinum majus) has long been a very popular perennial in the United States due to its unique flower shape with a range of striking colors (Huo and Chen, 2018). Based on their height, snapdragons are typically classified into three categories: dwarf (6-15 inches), medium (1-2 feet), and tall (6-15 feet) . The dwarf variety has a dense, bushy growth pattern, producing numerous flower spikes. They grow on average 6 to 15 inches tall and are ideal plants for use as low borders or in containers. Mid-sized varieties grow 1-2 feet tall and are typically used in borders (either alone or with other bedding plants) and sometimes as cut flowers. Tall varieties range anywhere from 2 to 3 feet in height (Gilman et al. 2018). The magnificent flowers with a wide range of petal colors atop the long green spikes make the tall variety a desirable cut flower for container, bouquets, or gardens. In 2015, fresh-cut snapdragon sales increased 51.7% from 2010 and reached $12.93 million, making it a top ten fresh cut flower in United States（USDA, 2015).